Properties and Potential Application of Urban Sewage Sludge as Construction Material in Da Nang City - Huan, Nguyen Xuan; Hoang Phat, Nguyen; Thi Minh Hang, Tran; Minh Trang, Hoang; Dinh Mau, Trinh; Manh Khai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2024)
Research on sludge properties makes an important contribution to the management and reuse of sludge for different purposes. In this study, 60 sludge samples were sampled from the urban drainage river system in Da Nang city and analyzed for their physical and chemical properties. The results show that the composition of the sludge samples are mainly sand, ranging from 52.2 to 90.1%, pH at slightly acidic to neutral levels, ranged from 4.3 to 6.8, total organic carbon content ranged from 1.1 to 6.0% and there was a large difference within samples. The content of Cl - , SO 4 2- ranges from 0.07 to 1.92%. There were 45/60, 31/60, and 26/60 samples with Zn, Pb and Hg contents exceeding the national technical regulation on sediment quality (QCVN 43:2017/BTNMT), respectively, from 1.04 - 2.52, 1.02 – 1.61, and 1.4 – 5.8 times. The As and Cd contents in all research samples were lower than the maximum allowable level (QCVN 43:2017/BTNMT). Ag, Co, and Se content were undetected in all samples. 48/60 sludge samples had phenol content exceeding QCVN 43:2017/BTNMT by 2.38 - 6.91 times. With this result, urban wastewater sludge in Da Nang city could be reused as bricked construction materials for a circular economy.